已知3x-4y-z=0,2x+y-8z=0,且z≠0,则x:y:z=( )

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 06:25:45
已知3x-4y-z=0,2x+y-8z=0,且z≠0,则x:y:z=()已知3x-4y-z=0,2x+y-8z=0,且z≠0,则x:y:z=()已知3x-4y-z=0,2x+y-8z=0,且z≠0,则

已知3x-4y-z=0,2x+y-8z=0,且z≠0,则x:y:z=( )
已知3x-4y-z=0,2x+y-8z=0,且z≠0,则x:y:z=( )

已知3x-4y-z=0,2x+y-8z=0,且z≠0,则x:y:z=( )
3x-4y-z=0 (1)
2x+y-8z=0 (2)
(1)+(2)×4得
11x-33z=0
∴x=3z
把x=3z代入(1)得
9z-4y-z=0
∴y=2z
∴x:y:z=3Z:2Z:Z=3:2:1

{3x-4y-z=0,2x+y-8z=0
解出y、z
{y=2/3x,z=1/3x
x:y:z=x:(2/3x):(1/3x)=3:2:1

3x-4y=Z,2x+y=8z
x=3z,y=2z且z≠0
则x:y:z= 3:2:1